1980
DOI: 10.4141/cjps80-097
|View full text |Cite
|
Sign up to set email alerts
|

Content and Distribution of Trypsin Inhibitors and Hemagglutinins in Some Legume Seeds

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
3

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(71 citation statements)
references
References 6 publications
4
64
0
3
Order By: Relevance
“…Total sulfur, methionine and cysteine contents varied significantly among different soybean genotypes. Genotype 'SL 688' exhibited maximum and significantly higher total sulphur and methionine contents as compared to other genotypes ( (Valdebouze et al 1980). Kumar et al (2003) reported that TI activity from defatted soy flour ranged from 42 to 113 mg g −1 and location effects on TI activity were nonsignificant.…”
Section: Resultsmentioning
confidence: 99%
“…Total sulfur, methionine and cysteine contents varied significantly among different soybean genotypes. Genotype 'SL 688' exhibited maximum and significantly higher total sulphur and methionine contents as compared to other genotypes ( (Valdebouze et al 1980). Kumar et al (2003) reported that TI activity from defatted soy flour ranged from 42 to 113 mg g −1 and location effects on TI activity were nonsignificant.…”
Section: Resultsmentioning
confidence: 99%
“…The titanium oxide content was measured using the colorimetric method described by Short et al (1996). The procedure to determine trypsin inhibitor was according to the method of Valdebouze et al (1980).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Trypsin inhibitor activity (TIA) (Valdebouze et al, 1980) was estimated in raw and extruded soyabean seeds.…”
Section: Measurementsmentioning
confidence: 99%